Level of Anxiety among Medical Students: A Descriptive Cross-Sectional Study (Nepal Journal of Health Sciences, 2023)
Introduction: Anxiety is one of the common psychological disorders showing more prevalence among medical students. Symptoms seen in the anxiety are excessive fear- worry and negative thoughts. In India and Pakistan have reported prevalence of anxiety consist of 66.9% and 44.7% % among undergraduate medical students, respectively. This study aims to find out the prevalence of anxiety among medical students.Objective: To assess the prevalence of anxiety among medical students of fourth year MBBS students of National Medical College and Teaching Hospital, Birgunj, Nepal.Method: A descriptive cross-sectional study was done to observe prevalence of anxiety in medical students of fourth year by using Hamilton Anxiety Rating Scale questionnaire. Data was entered and analyzed by the use of Statistical Package for Social Sciences version 20.0Result: The prevalence of anxiety among the students was found to be 70.4%, where as 64.3% students had mild and moderate anxiety, 6.1% of them had severe anxiety. The prevalence of anxiety among male students was 53.6%.Conclusion: Anxiety of prevalence was high among medical students. Rate of anxiety was more in male.